Proceedings of the 1st International Conference on Mechanical Engineering and Material Science 2012
DOI: 10.2991/mems.2012.179
|View full text |Cite
|
Sign up to set email alerts
|

Review on research and development of heat resistant Magnesium alloy

Abstract: Magnesium alloys as the emerging commercial metal structure material have excellent specific properties and stability, which is more and more important for researcher. The magnesium alloy of Mg-Al series, Mg-Zn series, Mg-RE series included Mg-Y series alloy, Mg-Gd-Y series alloy, Mg-RE-Zr series alloy, Mg-RE-Ag series alloy were summarized, the existing heat resistant magnesium alloy still exists insufficient heat resistance or poor comprehensive mechanical properties and processing property except heat-resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, there is a significant decline in the mechanical properties at elevated temperatures and the creep resistance at temperatures above 393 K is inadequate for most applications. More studies have shown the poor elevated temperature creep properties of Mg-Al based alloys is due to discontinuous grain boundary precipitation of β phase (Mg17Al12) from the supersaturated α-Mg solid solution and coarsening of β in the interdendritic eutectic region at high temperatures [1,2] .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a significant decline in the mechanical properties at elevated temperatures and the creep resistance at temperatures above 393 K is inadequate for most applications. More studies have shown the poor elevated temperature creep properties of Mg-Al based alloys is due to discontinuous grain boundary precipitation of β phase (Mg17Al12) from the supersaturated α-Mg solid solution and coarsening of β in the interdendritic eutectic region at high temperatures [1,2] .…”
Section: Introductionmentioning
confidence: 99%
“…20−25 It has been reported that the addition of aluminum (Al) into magnesium increases the ductility, yield strength, and ultimate tensile strength via the formation of β-Mg17-Al12 phase. 26,27 Al is commonly used as an alloying element with Mg and its concentration ranges between 2 and 9 wt % in commercially available Mg−Al alloys. 28 Regarding the biocompatibility of Al, good cytocompatibility for Mg−Al alloys as AZ91 has been proven in preosteoblastic MC3T3 cell lines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The process of alloying elements with Mg leads to an improvement in both corrosion resistance and corrosion rate in comparison to pure Mg, , and it has been shown to promote excellent biocompatibility in physiological conditions. It has been reported that the addition of aluminum (Al) into magnesium increases the ductility, yield strength, and ultimate tensile strength via the formation of β-Mg17-Al12 phase. , Al is commonly used as an alloying element with Mg and its concentration ranges between 2 and 9 wt % in commercially available Mg–Al alloys . Regarding the biocompatibility of Al, good cytocompatibility for Mg–Al alloys as AZ91 has been proven in preosteoblastic MC3T3 cell lines. , …”
Section: Introductionmentioning
confidence: 99%